On the Piezo‐Phototronic Effect in Si/ZnO Heterojunction Photodiode: The Effect of the Fermi‐Level Difference. (18th September 2020) - Pan, Zijian; Peng, Wenbo; Li, Fangpei; Cai, Yahui; He, Yongning
Abstract: The piezo‐phototronic effect has been extensively investigated to improve the performance of optoelectronic devices. However, the modulations in different energy band structures are quite distinctive, and adverse effects may be produced. Therefore, it is essential to investigate the modulation law in the optoelectronic devices with different energy band structures. Here, five kinds of Si/ZnO heterojunction photodiodes (PDs) with different energy band structures are fabricated and the piezo‐phototronic effect is systematically investigated on their photoresponse performance. For the p‐Si/n‐ZnO PDs, significant performance improvement is achieved by the piezo‐phototronic effect, with the magnitude of improvement increasing with doping concentration of p‐Si. For the n‐Si/n‐ZnO PDs, performance improvement is only achieved when the n‐Si is lightly doped, with a lower magnitude compared to that of the p‐Si/n‐ZnO PDs. The in‐depth working mechanism regarding to the different energy band structures is revealed. It is concluded that when the Fermi‐level of Si moves from the bottom of conduction band to the top of the valence band, the magnitude of performance improvement in Si/ZnO heterojunction PD increases. This study not only presents an in‐depth understanding regarding the piezo‐phototronic effect in Si/ZnO heterojunction PDs, but also provides guidance to optimize the piezo‐phototronic effect in optoelectronic devices. Abstract : The piezo‐phototronic effect is introduced to improve the performance of Si/ZnO heterojunction photodiodes with different Fermi‐levels in Si. It is found that when the Fermi‐level of Si moves from the bottom of the conduction band to the top of valence band, the magnitude of the performance improvement in Si/ZnO heterojunction PD is increased.